2021
DOI: 10.1038/s41598-021-94709-0
|View full text |Cite
|
Sign up to set email alerts
|

Passive repetitive stretching is associated with greater muscle mass and cross-sectional area in the sarcopenic muscle

Abstract: Mechanical stimulation has benefits for muscle mass and function. Passive stretching is widely performed in clinical rehabilitation medicine. However, the hypertrophic effects of passive repetitive stretching on senescent skeletal muscles against muscle atrophy remain unknown. We used senescence-accelerated model SAM-P8 mice. The gastrocnemius muscle was passively repetitive stretched by manual ankle dorsiflexion for 15 min, 5 days a week for 2 weeks under deep anesthesia. We examined the effects of passive st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…A recent study also revealed that 2 weeks of passive stretching (with a frequency of 15 min/ day for 5 days/week) prevented muscle loss in senescenceaccelerated mouse models. 26 The current results also found that increased flexibility during 4 years was associated with incident low muscle mass, low muscle strength and sarcopenia. Our findings suggested that maintaining high flexibility and monitoring the dynamic change of flexibility are both helpful in preventing sarcopenia.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…A recent study also revealed that 2 weeks of passive stretching (with a frequency of 15 min/ day for 5 days/week) prevented muscle loss in senescenceaccelerated mouse models. 26 The current results also found that increased flexibility during 4 years was associated with incident low muscle mass, low muscle strength and sarcopenia. Our findings suggested that maintaining high flexibility and monitoring the dynamic change of flexibility are both helpful in preventing sarcopenia.…”
Section: Discussionsupporting
confidence: 71%
“…In addition, we found that baseline flexibility was associated with 4‐year changes in SMI and HGS in the sensitivity analyses. A recent study also revealed that 2 weeks of passive stretching (with a frequency of 15 min/day for 5 days/week) prevented muscle loss in senescence‐accelerated mouse models 26 …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…For evaluation of MCSA the mean of the three highest MCSA values in the lateral and the medial head of the gastrocnemius were used to minimize potential error of location (Koppenhaver et al, 2009;Teyhen and Koppenhaver, 2011). Reliability of MRI measurements can be assumed as very high with r = 0.99 (Wirth et al, 2007;Wang et al, 2021).…”
Section: Sonographymentioning
confidence: 99%
“…In denervated muscles, stretching or contracting increases the expression of IGF-1 mRNA in myocytes and elevates the concentration of IGF-1, which activates Akt via an autocrine/paracrine mechanism (Agata et al., 2009). Akt activation facilitates muscle protein synthesis via mTOR, which also reduces the upregulation of ubiquitin-proteasome genes (activators of protein degradation) and maintains the level of runt-related transcription factor-1 (controls autophagy) (Hadj-Saïd et al., 2012), by negatively regulating forkhead-related transcription factor (Wang et al., 2021).…”
Section: Passive Muscle Movements Exercises and Muscle Massagementioning
confidence: 99%